Prolonged Cholestatic as a Typical Manifestation of Hepatitis A Infection: Diagnosis and Management - Nikko Darnindro; Rinaldi A Lesmana (The Indonesian Society for Digestive Endoscopy, 2013)
Hepatitis A virus (HAV), a positive-strand RNA virus, is stable at moderate temperature and low pH level. These characteristics allow the virus to survive in the environment and be transmitted through fecal-oral route.Twenty-year-old male came with jaundice and itchy skin since one month before admission. He was diagnosed as hepatitis A cholestasis type according to his history taking, physical examination, and laboratory result. Blood test showed elevated total bilirubin 27.4 g/dL, direct bilirubin 21.2 g/dL, indirect bilirubin 6.2 g/dL, alanin aminotransferase (ALT) 95 U/L, aspartate transaminase (AST) 134 U/L, alkaline phosphatase (ALP) 221 U/L, and gamma-glutamyltransferase (gGT) 17 U/L. His ultrasound results showed mild, non-specific hepatomegaly without common bile duct dilatation. The patient got symptomatic therapy with ursodeoxycholic acid (UDCA) 300 mg twice daily for his itchy skin and steroid therapy 0.5-1 mg/kg per day on the tenth day. He did not vomit or feel nausea anymore. After five days of steroid therapy, his total bilirubin level became 10.83 g/dL. He was discharged home with steroid therapy and steroid was tapered off during follow-up in the clinic.Prolonged cholestasis is one of atypical manifestation of hepatitis A which is rarely found. Cholestasis increases morbidity and prolongs hospitalization. Steroid therapy decreased bilirubin level and gave clinicalimprovement to the patient.Keywords: hepatitis A, prolonged cholestasis, steroid therapy